2016
DOI: 10.7498/aps.65.038402
|View full text |Cite
|
Sign up to set email alerts
|

Damage effects and mechanism of the GaN high electron mobility transistor caused by high electromagnetic pulse

Abstract: As electromagnetic environment of semiconductor device and integrated circuit deteriorates increasingly, electromagnetic pulse (EMP) of device and damage phenomenon have received more and more attention. In this paper, the damage effect and mechanism of the GaN high electron mobility field effect transistor(HEMT) under EMP are investigated. A two-dimensional electro-thermal theoretical model of GaN HEMT under EMP is proposed, which includes GaN polarization effect, mobility degradation in large electric field,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…where X, Y, and Z represent the coordinate directions of the device; P SP stands for spontaneous polarization effect; P PE stands for piezoelectric polarization; e 31 , e 33 , c 13 , and c 33 stand for piezoelectric coefficient and elasticity coefficient, respectively; a 0 stands for strain lattice constant; a stands for unstrained crystalline constant; and relax is the relaxation parameter [22,23]. In addition to this, trap effects and other physical models were included in the model.…”
Section: Physical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…where X, Y, and Z represent the coordinate directions of the device; P SP stands for spontaneous polarization effect; P PE stands for piezoelectric polarization; e 31 , e 33 , c 13 , and c 33 stand for piezoelectric coefficient and elasticity coefficient, respectively; a 0 stands for strain lattice constant; a stands for unstrained crystalline constant; and relax is the relaxation parameter [22,23]. In addition to this, trap effects and other physical models were included in the model.…”
Section: Physical Modelsmentioning
confidence: 99%
“…Subsequently, the mean free path of the carriers was raised, and the device began to be affected by the hot electron emission current. Since the hot electron emission current density was positively correlated with temperature and independent of the applied voltage [22], accelerating the increase in the device temperature, this was more likely to cause a breakdown. Therefore, the high domain-limiting characteristics of the double heterojunction permitted the electron injection efficiency to be increased, the transport efficiency to be improved, and the leakage current to be reduced.…”
Section: Physical Characteristics Of the Devicementioning
confidence: 99%
“…The influence of HPM on modern semiconductor devices and circuit systems has received increasing attention. [2][3][4][5][6][7][8][9][10][11][12] A simulation of a bipolar junction transistor (BJT) with the high electromagnetic pulses injection from the collector was simulated by utilizing the finite difference time domain method in two dimensions, the results indicated that the damage spot lay between the emitter and the collector where the avalanche breakdown occurs. [13] The transient response characteristics were simulated using the improver two-dimensional semiconductor device simulation program in order to obtain the damage effect of the BJT under the injection of electromagnetic pulse, which showed that the peak temperature appears on the edge of the emitter.…”
Section: Introductionmentioning
confidence: 99%